The Helminths of Wild Predatory Mammals of Ukraine. Cestodes - Kornyushin, V.V.; Malyshko, E.I.; Malega, A.M. (Вестник зоологии, 2011)
Data related to cestodes (totally 17 species), registered in predatory mammals in Ukraine are given and summarized. The richest cestode fauna was found in the Polissya region (Zhitomir, Kiev, Chernigov, Sumy Oblasts), Carpathian region and Transcarpathia. A wide host range characterizes the majority of cestodes occurring in predatory mammals of Ukraine. They are registered in both canines (Canidae) and felines (Felidae). Cestodes of the fox (9 species) and wolf (11 species) were studied more comprehensively. Other species of predatory mammals were infected with 1 to 3 species of cestodes. Приведены и обобщены данные, касающиеся цестод (всего 17 видов), зарегистрированных у диких хищных млекопитающих в Украине. Самая богатая цестодофауна отмечена в полесских областях (Житомирская, Киевская, Черниговская, Сумская), Карпатском регионе и Закарпатье. Большинство цестод, встречающихся у хищных млекопитающих Украины, характеризуются широким кругом хозяев и регистрируются как у псовых, так и у кошачьих. Наиболее полно изучена цестодофауна лисицы (зарегистрировано 9 видов цестод) и волка (зарегистрировано 11 видов цестод), остальные виды хищних млекопитающих исследованы в меньшем количестве (обнаружено 1—3 вида цестод).